Pengaruh Umur Terhadap Persentase Karkas dan Non Karkas Ternak Kerbau Jantan - Iskandar, Iskandar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
The aim of this research was to investigate carcass and non-carcass persentation of buffalo bull slaughtered in Kota Jambi Slaughter House. Sixty buffalo bulls consisted of 30 two-pair incissor bulls (I2) and 30 four-pair incissor bulls (I4). The data collected were body weight, carcass weight, non-carcass weight. Body weight of I2 was 338.56 ± 18,5 kg and I4 was 397.48 ± 45,5 kg. The carcass weight were  148.56 kg (43.89%) and 169,36 kg (43.72%) for I2 and I4 respectively. Non-carcass weigth were 137,40 kg (43,89%)  in I2 and 157,19 kg ( 40,57 %) in I4 . In conclusion, the age had no effect to carcass and non-carcass weight in buffalo bulls.